Travail d’organisation du lean manufacturing et santé : à la source des risques - Sébastien Bruère (Perspectives Interdisciplinaires sur le Travail et la Santé)
The aim of this paper is to open the debate about the relationship between occupational health and how the organization is built in lean manufacturing. Through a literature review, we have identified a number of organizational devices in lean system with paradoxical effects on health. In this work, we seek, in theory, ways to influence the organizing work that leads to the paradoxical effects in the implementation of the devices. In this research, we find that lean and system production rationalization have frameworks to the organizing act. Frameworks which themselves are carriers of paradoxical effects on work and health.